Effects of Boundary Conditions on the Modal and Spectral Properties of the Shaft - Hruby, Petr; Nahlik, Tomas; Smetanova, Dana (Communications - Scientific Letters of the University of Zilina, 2020)
Influence of boundary conditions (i.e. mounting type of shafts ends) on spectral and modal properties is studied in this paper. Cases with joints at both ends and with joint at one end and fixed end are described in detail. The vibration problem of rotating shaft is generalized to problem of vibration of the shaft in the rotating plane. The problem is illustrated on testing models. The real mounting type of shafts is presented.
Keywords: shaft; boundary conditions; critical velocity; deflection; vibration